Analisis Tingkat Berfikir Kreatif Peserta Didik Dalam Menyelesaikan Soal Matematika Ditinjau Dari Adversity Quotient (AQ) - Duwi Asih asih; I Ketut Suastika; Nyamik Rahayu Sesanti (Fakultas Sains & Teknologi Universitas Kanjuruhan Malang, 2019)
ABSTRAK. The aim of this paper is to describe students' creative thinking abilities in solving problems in terms of Adversity Quotient (AQ). This study used a descriptive qualitative approach with questionnaire and test method. The subjects of this study were SMP Turen Muhammadiyah 10 class VIII, who were selected based on their Adversity Quotient (AQ). The results of this paper are (1) the questionnaire score of the Adversity Response Profile (ARP) shows 6 students with the type of quitters, 7 transitional type students between quitters to campers, 9 students with type campers, 6 students with transition types of campers to climbers , 4 students with type climbers. (2) The written test results showed students with AQ type climbers included in the